2006
DOI: 10.1634/theoncologist.11-10-1095
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Given Near the End of Life by Community Oncologists for Advanced Non-Small Cell Lung Cancer

Abstract: Purpose. To characterize the chemotherapy given near the end of life to advanced non-small cell lung cancer (NSCLC) patients treated in the community oncology setting using a medical records database. Results. We report data from 10 community practices including 417 patients treated for advanced NSCLC in 2000-2003. The mean age was 67 years (median, 62 years) and 54% were male. Forty percent of patients were >69 years of age and 35% had an Eastern Cooperative Oncology Group performance status score of ≥2.First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 17 publications
10
66
1
2
Order By: Relevance
“…The current study's respondents also reported that the aggressive treatment received by patients at end of life in their practice settings was quite common, consistent with current literature (Braga et al, 2005;Earle et al, 2004Earle et al, , 2008Murillo & Koeller, 2006). Similiarly, respondents stated that most patients with advanced cancer in their practice did not have advanced care planning discussions with clinicians, and many continued to receive active chemotherapy during last month of life with only a minority using hospice care.…”
Section: Discussionsupporting
confidence: 81%
“…The current study's respondents also reported that the aggressive treatment received by patients at end of life in their practice settings was quite common, consistent with current literature (Braga et al, 2005;Earle et al, 2004Earle et al, , 2008Murillo & Koeller, 2006). Similiarly, respondents stated that most patients with advanced cancer in their practice did not have advanced care planning discussions with clinicians, and many continued to receive active chemotherapy during last month of life with only a minority using hospice care.…”
Section: Discussionsupporting
confidence: 81%
“…of chemotherapy cycles 7 15 In this study, the subgroup analysis showed that 49 patients were treated with less than second-line chemotherapy and 33 patients (40.2%) were treated with more than third-line chemotherapy. this result is similar to that of Murillo and Koeller, who also reported that 41% patients received more than third-line chemotherapy (9).…”
Section: Discussionsupporting
confidence: 91%
“…They have also undergone testing in other health care settings and in other countries. 7,8 One reason for this interest is that they have the relatively unique feature of assessing overuse. Oncologists have traditionally focused on underuse (surgery, adjuvant chemotherapy or radiation) as the source of most quality problems, with little attention to the possibility that overuse could result in poor quality care.…”
Section: "Continuation Of Chemotherapy Very Near Death May Indicate Omentioning
confidence: 99%